REFLECTION ON TEACHING A POSTGRADUATE, PROJECT-BASED LEARNING COURSE WITH DIVERSE DISCIPLINES - Shiwakoti, Nirajan; Stasinopoulos, Peter (PEOPLE: International Journal of Social Sciences, 2020)
This paper is a teaching reflection on the delivery of the postgraduate, project-based learning (PBL) engineering course (subject) that is common to five Masters of Engineering program at School of Engineering, RMIT. The data was sourced from end-of-semester surveys of the perceptions of students who completed the course between 2017, when we taught the course for the first time, and 2019. The analysis showed substantial improvements in overall satisfaction, percentage of agreement on the project-based learning helping students to work well with peers, and percentage of agreement that students became more able to apply the theories to practice. The mastery in teaching such a course, especially when the students from various disciplines are involved, demands an adaptive teaching approach wherein the instructors or teachers experiment to continuously improve on the shortcomings in subsequent offerings to enhance the students’ learning experience. A PBL course that is well-designed, well-supported, well-implemented, and well-taught can engage students by improving their comprehension, helping them to work well with peers, improving their communication, and assisting them to apply theories to real application or practice.